Belajar matematika tanpa stres: Tips dan trik belajar matematika secara efektif - Salsabila, Dani Dwi (Maliki Interdisciplinary Journal, 2024)
This research provides knowledge on effective methods for learning mathematics. A qualitative method is used in this research to describe and give clear and concise explanations about tips and tricks for learning mathematics, including determining the time and place for studying, taking notes and understanding formula concepts, using memory and analysis techniques, forming study groups, being brave enough to ask questions, using various resources, and frequently practicing problems. By applying these tips and tricks, readers are expected to improve their math skills in an enjoyable way without pressure and stress.